Landscape Mapping, Ichnological and Benthic Foraminifera Trends in a Deep-Water Gateway, Discovery Gap, NE Atlantic - Dorokhova, Evgenia V.; Rodríguez-Tovar, Francisco J.; Dorokhov, Dmitry V.; Kuleshova, Liubov A.; Mena, Anxo; Glazkova, Tatiana; Krechik, Viktor A. (Geosciences (Basel), 2021)
Multidisciplinary studies have allowed us to describe the abiotic landscapes and, thus, reveal the ichnological and benthic foraminifera trends in a deep-water gateway. Mesoscale landscape mapping is presented based on the bathymetric position index, substrate types and near-bottom water temperature. Four sediment cores, retrieved from the entrance, centre and exit of the gap, were subject to computed tomography, ichnological and benthic foraminifera studies. A high diversity of abiotic landscapes in the relatively small area of Discovery Gap is detected and its landscape is characterized by 23 landscape types. The most heterogeneous abiotic factor is a topography that is associated with sediment patchiness and substrate variability. The ichnological and tomographical studies of the sediment cores demonstrate lateral and temporal differences in the macrobenthic tracemaker behaviour. The ichnofossils assemblage of the sediment core can be assigned to the Zoophycos ichnofacies with a higher presence of Zoophycos in the entrance site of the gap and during glacial intervals. Higher benthic foraminifera diversity and species richness during the Holocene are also registered in the southern part of the gap compared to the northern part. The spatial and temporal differences in macro-benthos behavior and benthic foraminifera distribution in the deep-water gateway are proposed to relate to the topographical variations of the Antarctic Bottom Water and its influence on the hydrodynamic regime, nutrient transport, etc.